Analisis Good Governance Organisasi Pengurus Provinsi Hapkido Indonesia Jawa Tengah - Hartono, Mugiyo; Kusuma, Donny Wira Yudha; Yuda, Luisiana Nosa (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to show how transparency is good governance, the democratic process is good governance, checks and balances are good governance, and solidarity is good governance of the Central Java Indonesian Hapkido Management organization. The research uses qualitative research with an ethnographic analysis design—an action instrument for good governance in international sports organizations (AGGIS). They were analyzed using the Sports Governance Observer (SGO) Index. The data source obtained was information from the Pengprov organization and the Central Java Hapkido platda trainers. Data collection techniques include observation, interviews, and documents. The research results show that the organizational management period in one is four years. There are 13 members of the organization, 14 Platda Athletes, and 3 Platda trainers. The percentage results of the four dimensions of good governance are (61%) with each dimension as follows: Transparency (0%), Democratic Process (91%), Checks and Balances (80%), and Solidarity (76%). The level of good governance of the Central Java Hapkido Provincial Government is in the Good category because the percentage level of the four dimensions of good governance (61%) is between 61% - 80%, namely Good. However, the transparency level of 0.00 = 0% is not transparent. In conclusion, the level of good governance of the Central Java Hapkido Provincial Government is good. Keywords: Good Governance, Hapkido, Organization, esain berupa analisis ethnography. Intrumen Action for Good governance in International Sports Organization (AGGIS). Dan dianalisis menggunakan Sports Governance Observer (SGO) Indeks. Sumber data yang diperoleh berupa informasi dari organisasi Pengprov dan pelatih platda Hapkido Jawa Tengah Hapkido. Teknik pengumpulan data adalah, observasi, wawancara dan dokumen. Hasil penelitian, Pengprov Hapkido Jawa Tengah beralamat di Jl. Supriyadi No.B-11, Kalicari, Kec. Pedurungan, Kota Semarang, Jawa Tengah 50198. Masa kepengurusan organisasi dalam satu periode adalah 4 tahun. Anggota organisasi berjumlah 13 orang, Atlet Platda berjumlah 14, pelatih platda berjumlah 3. Hasil persentase dari empat dimensi good governance yaitu (61%) dengan masing-masing dimensi sebagai berikut: 1) Transparency (0%). 2) Democratic Process (91%). 3) Checks and Balances (80%). dan 4) Solidarity (76%). Menunjukan tingkat good governance Pengprov Hapkido Jateng kategori Baik, karena tingkat persentase dari empat dimensi good governance yaitu (61%) berada diantara 61% - 80% yaitu Baik. Namun, tingkat transparansinya 0,00 = 0% bisa dikatakan tidak transparan. Simpulan, tingkat good governance Pengprov Hapkido Jateng adalah baik. Saran, dengan adanya penelitian ini peneliti tidak bermaksut membuat Pengprov Hapkido Jateng terkesan tidak baik di masyarakat. Namun ini menjadi awal sebagai bahan evaluasi Pengprov Hapkido Jateng. Dan sudah seharusnya Pengprov Hapkido Jateng memiliki website supaya dunia digital sebagai informasi yang baik dapat tersebar dan dapat di ketahui oleh masyarakat serta untuk meningkatkan keterbukaan sebuah organisasi. Kata Kunci: Good governance, Organisasi, Hapkido.